Epstein–Barr virus associated peri-implantitis: a split-mouth study - Verdugo, Fernando; Castillo, Ana; Castillo, Francisca; Uribarri, Agurne (Clinical oral investigations, 2015)
Objectives Herpesviral–bacterial synergism may play a potential role in periodontitis and peri-implantitis (PI) etiopathogenesis. PI lesions can worsen depending on specific microbial challenge and host susceptibility. This cross-sectional split-mouth study aimed to substantiate herpesviral–bacterial co-infection in PI patients and assess associations with periodontopathogen salivary contamination. Methods PCR-based identification was performed on 23 patients presenting PI and contralateral healthy implants, and compared to unstimulated whole saliva. Clinical evaluation included probing depths, bleeding on probing, and suppuration. Radiographs were assessed for the presence of lamina dura and bone loss. Three sample sites per patient were tested: PI lesions, healthy implant sulci, and saliva. Quantitative PCR evaluated Epstein–Barr virus (EBV) and cytomegalovirus (CMV) copy counts. Significance of group comparisons for binary-dependent variables, within-subjects designs, was determined by McNemar's chi-square test. Risk analysis was evaluated through odds ratios (OR). Results PI lesions were 14.2 ( P = 0.001; 95 % confidence interval [CI], 1.6–124.1) and 3 times ( P = 0.03; 95 % CI, 0.7–11.9) more likely to harbor EBV than healthy implants and saliva, respectively. EBV positive predictive value was 90 %. PI was associated with absence of lamina dura and higher periodontopathogen proportions. Saliva sampling showed high agreement with PI bacterial detection (89–100 % rate) but not with EBV (44.4 %). The OR of PI lesions harboring Treponema denticola or Tannerella forsythia was 6.79 ( P = 0.007; 95 % CI, 1.8–25.0) and 3.3 ( P < 0.0001; 95 % CI, 0.3–34.3) times higher than healthy implants, respectively. Saliva of patients with PI was 5.6 times more likely to be contaminated with Prevotella nigrescens than healthy peri-implant sulci ( P = 0.002). PI lesions were 1.92 times more likely to harbor Prevotella nigrescens than healthy implants ( P = 0.04). Conclusions EBV is a potential candidate in peri-implantitis etiopathogenesis. Saliva PCR analysis is useful in predicting peri-implantitis-specific bacterial infection but not EBV or CMV. Clinical significance Herpesviral–bacterial synergism may favor ongoing microbial challenge in peri-implant disease and exacerbate its progression. EBV infection may explain non-responsive to treatment PI. Peri-implantitis individuals may benefit from antiviral therapy.